The Development of Innovative Mindset for Enhancing Organization Culture Literacy of Employees in the Large Private Multinational Water Solution Company Sector - Ploikrajang, Navasanant; Kirdpitak, Pongpan; Malakul Na Ayudhya, Prasarn (The Periodical of Behavioral Science, 2023)
This research was a mixed method research. The purposes of this research were 1) to study of organization culture literacy of employee in the large private multinational water solution company sector, 2) to develop innovative mindset for enhancing organization culture literacy, and 3) to study the effect of innovative mindset for enhancing organization culture literacy of employees. The population of this study was 101 employees of the large private multinational water solution company sector. The sample included two groups; the first group of organization culture literacy study consisted of 81 employees stratified selected from the population. The second group was purposely selected from the first group. This group consisted of 40 employees whose organization culture literacy scores were lower than fifty percentiles. They were then randomly assigned into 2 groups, classified as an experimental group and a control group, 20 persons in each group. The experimental group participated in the innovative mindset while the control group did not receive the innovative mindset and engaged in ordinary work. The research instrument were 1) the scale of organization culture literacy and 2) the innovation mindset for enhancing organization culture literacy. The quantitative data analyses were mean, standard deviation, Normality test, One-Way ANOVA with Repeated measure, Two-Way ANOVA with Repeated measure, and the qualitative data analysis was focus-group discussion. The results of the study were 1) the organization culture literacy of 81 employees revealed high with average score of 39.97 (39.97±8.24), 2) the innovative mindset was developed by applying psychological concepts: future orientation, holistic reflection, and design thinking and 3) post-test and follow-up of the organization culture literacy of the experimental group were significantly higher than pretest at the .01 level (F=54.226, p<.01) and significantly higher than that of the control group at .01 level (F=194.761, p<.01)